Person-Centered Therapy for the Recovery of Social Alienation in a Student with Internalized Conditions of Worth: A Case Study - Reza Pahlevi; Dona Fitri Annisa; Yusi Riksa; Nur Sholehah Dian Saputri (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Academic pressure among students has become a significant psychological concern, particularly in cultures where academic success is closely linked to personal worth and social recognition. In such environments, strong parental expectations may be internalized as conditions of worth, leading individuals to believe they are valued only when they meet specific standards. This internalization can create incongruence between the real self and the ideal self, which often manifests as anxiety, perfectionism, low self-esteem, and social withdrawal. Objective: This study aims to examine the formation of internalised conditions of worth and to analyze how Person-Centred Therapy (PCT) facilitates psychological recovery and self-concept reconstruction. Method: The study employed a qualitative, single-case study design with a high school student experiencing social alienation and achievement-contingent self-worth. Data were collected through semi-structured counseling interviews, classroom observations, and psychological assessments, and analysed using thematic analysis to identify patterns related to self-concept and family expectations. Result: The findings revealed that conditional acceptance related to academic achievement contributed to a fragile self-concept and social withdrawal. Through empathy, congruence, and unconditional positive regard, PCT supported emotional openness and reduced self-criticism. Conclusion: Person-Centred Therapy effectively facilitated self-acceptance and reduced social alienation. Contribution: This study provides practical insight for school counseling interventions addressing conditional self-worth among students.